Seasonality of the activity pattern of Callithrix penicillata (Primates, Callitrichidae) in the cerrado (scrub savanna vegetation) - Vilela, S. L. (2004)
Two wild groups of Callithrix penicillata, the Black Pincelled Marmoset, were observed from January to September 1998, in two areas, one an area of dense scrub savanna vegetation (cerrado) and the other, a semidecidual woodland (cerradão), both within the boundaries of the Ecological Reserve of IBGE (Brazilian Institute of Geography and Statistics), in an environmentally protected area, the APA (Portuguese abbreviation for "environmental protected area") Gama/Cabeça-de-Veado, Brasília, DF. The behavioral data collected during the rainy (January 15 to April 15) and dry season (June 1 to September 15) were compared. Because of the proximity to the Reserve facilities, the group from the dense scrub savanna vegetation (CD) was submitted to antropic impacts different from the group in the semidecidual woodland (CE), which was using as territory an area that had been suffering from man-made fires every two years as part of a long-term experimental project on fire impacts. The behavioral data was quantified by instantaneous cross-section ("scan sampling") every ten minutes with records of locomotion, rest, foraging for insects, use of exudate, and feeding. During the whole year, the greatest percentage of time spent by CE and CD was in foraging for insects, with 44% and 39%, respectively. It was evident when comparing the data for the two seasons that, for both groups, foraging for insects was more intense during the dry season, possibly to complement the shortage of food, and locomotion increased during the rainy season. The greater the availability and distribution of fruit in the areas, the greater the locomotion of the groups to obtain these resources. None of the other behavioral patterns, including the use of exudates, presented significant differences between the two seasons. Both groups foraged more frequently during the dry season and locomoted more during the rainy one.